Answer:
The polynomial is;
P(x) = 0.2(x^3-9x^2+ 24x - 16
Explanation:
Here, we want to write the formula for the polynomial
We start by equating the roots to zero
x = 4 becomes x-4
x = -1 becomes x + 1
The expression here will be;
P(x) = a (x-4)^2(x+ 1)
P(x) = a { (x-1)(x^2-8x + 16)}
P(x) = a{ x^3-8x^2+16x-x^2+8x-16}
P(x) = a {x^3-9x^2+24x-16}
To get the value of a, set x = 0 and P(x) to -3.2
This is because the value of x at the y-intercept is 0
So we have that;
-3.2 = a(-16)
a = -3.2/-16
a = 0.2
So the polynomial will project as planned.
P(x) = 0.2(x^3-9x^2+ 24x - 16